2020
DOI: 10.1002/ffj.3599
|View full text |Cite
|
Sign up to set email alerts
|

Effect of natural spices on precursor substances and volatile flavor compounds of boiled Wuding chicken during processing

Abstract: Boiled chicken with spices is a traditional and characteristic meat product in China. The aims of this work were to investigate the influences of natural spices on precursor substances, and the volatile flavor compounds of boiled Wuding chicken were studied. Whole, boiled Wuding chicken was processed by washing the chickens, boiling them for 1 hour with natural spices, then deep‐frying for 1 minute, and boiling them for 2 hours with natural spices. The water‐soluble low molecular weight (WLOM) compounds in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…Headspace-gas chromatography-ion mobility spectrometry (HS-GC–IMS) is a specific and simple method for identifying VOCs. Recently, HS-GC–IMS has been proven to be a helpful approach for analyzing and recognizing VOCs with different characteristics in foods, including dry-cured fish [ 11 ], Tricholoma matsutake Singer [ 12 ], sea cucumber peptide powders [ 13 ], peppers [ 14 ], and boiled Wuding chicken [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Headspace-gas chromatography-ion mobility spectrometry (HS-GC–IMS) is a specific and simple method for identifying VOCs. Recently, HS-GC–IMS has been proven to be a helpful approach for analyzing and recognizing VOCs with different characteristics in foods, including dry-cured fish [ 11 ], Tricholoma matsutake Singer [ 12 ], sea cucumber peptide powders [ 13 ], peppers [ 14 ], and boiled Wuding chicken [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al studied the effect of natural spices on the flavor substances of stewed Wuding chicken. The results showed that the content of the total fatty acids, water-soluble small molecular weight compounds and volatile flavor substances in the treatment group was significantly higher than that in the control group (p < 0.05) [32]. It could, therefore, be concluded that natural spices had a significant effect on the flavor precursor substances of boiled Wuding chicken.…”
Section: Marker Compound Analysismentioning
confidence: 80%
“…Yu et al evaluated the effects of spices on flavor compounds in the stewing process of Wuding chicken. The results showed that the addition of spices increased the water-soluble low molecular compounds, and exhibited a significant effect on the release of volatile compounds [ 28 ].…”
Section: Resultsmentioning
confidence: 99%